The nights of our young people. (Journal of Parents and Teachers, 2014)
Young people leave the night on Friday and Saturday and those who do not, are considered rare. Society accepts it naturally and parents educate their children from permissiveness, forgetting authoritative education. And in those nocturnal exits, the great companion is always the alcohol. The article explains why.
Keywords: Youth; night; permissiveness; alcohol.